Retratos de uma nação (Almanack, 2025)
Resenha: SARAIVA, Luiz Fernando, NABARRO, Wagner, GOLDFEDER, Pérola (orgs.). Atlas Histórico-econômico do Brasil no Século XIX. Brasília: Senado Federal; Niterói: Eduff, 2024.